Experimental Investigation of Delamination Growth in Composite Laminates under a Compressive Load. (5th July 2017) - Riccio, A.; Cristiano, R.; Mezzacapo, G.; Zarrelli, M.; Toscano, C.
Abstract : This paper focuses on the use of no-contact experimental techniques for monitoring the interlaminar damage evolution in composite laminates. Indeed, Infrared Thermography and Digital Image Correlation are adopted to investigate, in composite plates with artificial delamination, the influence of the delamination initial position on the delamination growth. The paper also investigates the feasibility of using a no-contact experimental technique for the measurement of displacement and strain during mechanical tests, such as the Digital Image Correlation, to evaluate, by means of indirect measurements, the delamination growth as a function of the applied load.